KEEFEKTIFAN PENGGUNAAN KUIS BERBASIS WEB 3G UNTUK PEMBELAJARAN SIMPLE PAST TENSES PADA SISWA KELAS X SMAN 4 KOTA BLITAR - Yuli Wahyuning Tyas; Hesty Puspita Sari; Nita Sutanti; Supriyono ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
Understanding tenses, particularly the Simple Past Tense, is essential for students' proficiency in English, yet many struggle due to the differences between English and Indonesian grammar. This study aims to determine the effectiveness of the 3G Web-Based Quiz in enhancing the learning of the Simple Past Tense among students of Class X at SMAN 4 Kota Blitar. This study uses a pre-experimental design with a one-group pretest-posttest methodology. Purposive sampling was used to select 36 students from SMAN 4 Kota Blitar's Class X J. Students' scores from before and after the treatment were compared to determine how effective the web-based quiz was. The student's performance significantly improved, as evidenced by the post-test results, with the average pre-test score of 61.03 increasing to 82.94 in the post-test. Statistical analysis using a paired sample t-test revealed a calculated significance value (Sig. 2-tailed) of 0.001, indicating < α 0.05. Therefore, Ho is rejected and Ha is accepted. This means that the pre-test and post-test scores differ significantly, indicating that 3G web-based quizzes effectively improve the learning achievement of Simple past tenses of class X students at SMAN 4 Blitar. The findings support the conclusion that 3G Web-Based Quizzes effectively improve the learning outcomes of the Simple Past Tense among high school students, making them a valuable tool for educators looking to improve grammar instruction.